1954
DOI: 10.1103/physrev.95.315
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Aurora Based on Magnetic Self-Focusing of Solar Ion Streams

Abstract: It is assumed that the sun emits a jet of an electrically neutral mixture of fast electrons and positive ions, and that the space between the sun and earth is filled with an ionized, electrically neutral gas. As the jet proceeds the fast electrons are slowed down and scattered by encounters with the space ionization, being continually replaced by slow electrons from space. The stream of positive ions continues as an electric current, but at all times the stream and surrounding gas are closely electrically neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1955
1955
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It is necessary that the cloud is almost exactly electrically neutral. The concept of a stream of highly charged plasma (that is, an electric current) emanating from the Sun, has recently been revived by BENNETT et al (1954), but has been criticized by Ferraro and appears unacceptable.…”
Section: Historicalmentioning
confidence: 99%
“…It is necessary that the cloud is almost exactly electrically neutral. The concept of a stream of highly charged plasma (that is, an electric current) emanating from the Sun, has recently been revived by BENNETT et al (1954), but has been criticized by Ferraro and appears unacceptable.…”
Section: Historicalmentioning
confidence: 99%
“…If the sun has a dipole magnetic moment M apart from the random multipolar fields that are observed on its surface [3], the resulting field will deflect a proton beam in its passage out to the earth. The word "beam" is used in view of the self-focusing action that can be expected in a current of fast protons [2]. S'mce the neutralizing electrons come from the interplanetary matter, they will follow *This work was assisted by the joint program of the U.S. Office of Naval Research and the U.S. Atomic Energy Commission.…”
Section: Effect Of'the Solar Dipolementioning
confidence: 99%
“…If the latter are caused by ion streams originating in the sun, as is generally believed, then this time lag implies stream velocities of about 1.5 X !0 8 cm sec -•. However, convincing evidence [2] has been presented in favor of the hypothesis that the streams actually consist of fast (i0 TM cm sec -•) protons accompanied by slow electrons to provide electrical neutrality. In this event, the time lags must be accounted for on some basis other than tr•vel time.…”
Section: Introductionmentioning
confidence: 99%
“…If the plasma moves through some other plasma, retardation of the electrons is much more strong than the retardation of protons. This was indicated by W. Bennet and E. Hulburt [6], who suggested that the stream must consist of highvelocity protons and slow electrons. However, such combination of different velocities represents an electrical current, the increase of which from zero being restricted by self-induction.…”
mentioning
confidence: 93%
“…If i/=o-2, the concentration TZ« io 6 , T&6 x io 6 degrees. The linear dimensions are reduced considerably and probably constitute some tens of kilometers.…”
mentioning
confidence: 99%